Using financial ratio to compare performance of the commercial and the Islamic banks Listed on Palestine Exchange - الشيخ علي مفيد خالد (Journal of Economics and Administrative Sciences, 2018)
The research aimed to compare the performance of the commercial and the Islamic banks listed in the Palestinian’s Stock Exchange .To achieve the objectives of the study we selected all the commercial and the Islamic banks listed in the Palestinian Stock Exchange to obtain the necessary data for the analysis process during the period of (2009-2013) .the comparison based on the performance indicators ( liquidity rate, profitability rate ,the activity rate and the market rate). a statistical method was used to analyze the date to find the performance differences between the commercial banks, and the Islamic banks. The results of the study showed that there were no statistical differences between the both banks on the fund liquidity rate, profitability rate, and the market rate). As for the activity rate that showed a statistically difference between the both banks and it was in favor of Islamic banks. The study has recommended a series of recommendations including urging commercial banks to invest their resources appropriately by investing their deposits, in addition to increasing its ability to turn its resources in general, as well as thinking seriously to open branches in accordance with the provisions of Islamic law, and the need to make seminars and workshops to illustrate how the Islamic banks work and to know its mechanism of work and its advantages.